The Effect of Bond-Slip in the Numerical Assessment of RC Frames Under Cyclic Loading - Lobo, Paulo S. (2017)
Bond-slip may have significant influence on the assessment, with numerical models, of reinforced concrete structures subjected to cyclic loadings, whether static or dynamic. Its influence is discussed with the correlation of experimental and analytical results, where two numerical models are considered, including a perfect bond fiber-section finite element formulation and a force-based fiber-section model including bond-slip in the vicinity of the frame joints, both exterior and interior. In this case, the model implemented makes it possible to consider the coupling effect of the response of the beams adjacent to the joint, and the models are constructed from the geometrical and material characteristics of the structure, without any calibration procedures. The experimental results are from a reinforced concrete column and a beam-column subassemblage, both subjected to static cyclic loadings, with predefined displacements sequences for the element-ends, and from a shaking table test of a one bay two-story reinforced concrete frame structure. The comparisons show that the considered bond-slip based model makes it possible to satisfactorily predict the response of reinforced concrete frames under both static and dynamic cyclic loadings. The influence of reinforcement slippage was evaluated by comparison of the previous results with those obtained with the perfect bond-based model. This made it possible to conclude that the accuracy of the model considering bond-slip is significantly superior to that of the perfect bond model. Furthermore, responses obtained with the previous model show the pinching effect, which is characteristic of reinforced concrete structures and significantly changes the hysteretic dissipated energy, not delivered by the latter model. This can also be seen in the effect of bond-slip in the response of the fibers which model the reinforcing rebars.